On the “Hippolyte commensalis Kemp, 1925” species complex (Decapoda, Caridea, Hippolytidae), with the designation of a new genus and description of two new species from the Indo-West Pacific - Marin, Ivan; Okuno, Junji; Chan, Tin-Yam (Zootaxa, 2011)
Only one species of hippolytid shrimp, namely Hippolyte commensalis Kemp, 1925, was previously known to be associated with alcyonacean soft corals (Octocorallia, Alcyonacea) in the Indo-West Pacific. Recent collections revealed that at least three distinct hippolytid species are associated with alcyonacean soft corals. Moreover, these alcyonacean-associated hippolytids differ considerably from all other species of the genus Hippolyte Leach, 1814 in having a smooth rostrum bearing a single subapical ventral tooth, reduced styliform incisor process of the mandible, the basal antennular segment without ventromedial tooth, and the ambulatory pereiopods lacking or with only relatively small distoventral spines. A new genus, Alcyonohippolyte gen. nov., is thus established for Hippolyte commensalis Kemp, 1925 and two new species. Alcyonohippolyte dossena sp. nov. (the type species of the new genus) mainly differs from the congeners in having a humpbacked carapace. Alcyonohippolyte maculata sp. nov. closely resembles A. commensalis but clearly differs in having a furry carapace and distinct coloration, as well as in association with different alcyonacean host. An identification key is provided as well as information on the live coloration and host for all species of Alcyonohippolyte gen. nov.